2016
DOI: 10.1363/48e8216
|View full text |Cite
|
Sign up to set email alerts
|

Utah's 72‐Hour Waiting Period for Abortion: Experiences Among a Clinic‐Based Sample of Women

Abstract: Introduction: This study investigates women's experiences with Utah's 72-hour waiting period and two-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 21 publications
9
49
1
Order By: Relevance
“…Adults provided informed consent; minors aged 15 to 17 could participate with parental consent and their own assent. Detailed methods have been described elsewhere [17] . In brief, eligible women were asked to complete a baseline survey on an iPad prior to an abortion information visit and a follow up interview by phone with University of California, San Francisco (UCSF) interviewers three weeks later.…”
Section: Sample and Study Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Adults provided informed consent; minors aged 15 to 17 could participate with parental consent and their own assent. Detailed methods have been described elsewhere [17] . In brief, eligible women were asked to complete a baseline survey on an iPad prior to an abortion information visit and a follow up interview by phone with University of California, San Francisco (UCSF) interviewers three weeks later.…”
Section: Sample and Study Proceduresmentioning
confidence: 99%
“…At the time that they completed the baseline survey, women had not yet had any interaction with a health care provider or counselor at the study clinic. The main goal of the overall study was to examine women's reasons for not having an abortion under the 72-hour waiting period and twovisit requirement [17]; thus, we aimed to recruit at least 75 women who completed an abortion information visit but did not return for an abortion. Previous research in a state without a two visit or waiting period requirement found that 7% of women seek but do not obtain an abortion [14].…”
Section: Sample and Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research has not found support for this argument (Roberts, Turok, Belusa, Combellick, & Upadhyay, 2016). In fact, we found that most women presenting for an abortion information visit under the 72-hour waiting period and twovisit requirement have made their decision when they presented for the information visit and go on to have an abortion .…”
Section: Introductionmentioning
confidence: 63%
“…It was developed in health care settings where people were considering whether to have an influenza vaccination or undergo breast cancer screening (O'Connor, 1993) and has been used in studies of decision making regarding prenatal testing (Caleshu, Shiloh, Price, Sapp, & Biesecker, 2010), breast cancer treatment (Banegas et al, 2013;King et al, 2013), vasectomy (Labrecque, Paunescu, Plesu, Stacey, & Legare, 2010), and bariatric surgery (Schauer et al, 2014), among others. The DCS also demonstrated appropriate reliability, as well as construct and predictive validity, among abortion patients predicting which patients would proceed to have an abortion vs. continue the pregnancy (Ralph, Foster, Kimport, Turok, & Roberts, 2016;Roberts et al, 2016).…”
Section: Methodsmentioning
confidence: 94%